Meta-Analytic Structural Equation Modeling of the Influences of Family-Centered Care on Parent and Child Psychological Health - Carl J. Dunst; Carol M. Trivette (Hindawi Limited, 2009)
Background. Family-centered care is now practiced throughout the world by physicians, nurses, and allied health care professionals. The call for adoption of family-centered care is based on the contention that the physical and psychological health of a child is influenced by parents' psychological health where family-centered care enhances parent well-being which in turn influences child well-being. We empirically assessed whether these relationships are supported by available evidence. Method. Meta-analytic structural equation modeling was used to test the direct and indirect influences of family-centered care and self-efficacy beliefs on parent and child psychological health. Data from more than 2900 parents and other caregivers in 15 studies were used for the analyses. Results. Family-centered care had indirect effects on parent and child psychological health mediated by self-efficacy beliefs. Conclusion. The relationships posited in the literature about family-centered care were supported by the study results.